Patient-reported Outcomes and Revision Rates at a Mean Follow-up of 10 Years After Lumbar Total Disc Replacement - Laugesen, Line A; Paulsen, Rune T; Carreon, Leah; Ernst, Carsten; Andersen, Mikkel Ø (Spine (Philadelphia, Pa. 1976), 2017)
Prospective observational cohort study. The aim of this study was to determine the long-term clinical results and prosthesis survival in patients treated with lumbar total disc replacement (TDR). Fusion has become the current standard surgical treatment for lumbar degenerative disease. TDR is an alternative treatment that seeks to avoid fusion-related adverse events, specifically adjacent segment disease. Sixty-eight consecutive patients treated with TDR from 2003 to 2008 were invited to follow-up and complete a Visual Analog Scale (VAS) for back and leg pain, the Dallas Pain Questionnaire (DPQ), and the Short Form-36. These surveys were also administered to the subjects before their index TDRs. Data on reoperation were collected from the patients' medical records. Fifty-seven (84%) patients were available for follow-up at a mean 10.6 years post-operatively (range 8.1-12.6 years). There was a significant improvement from preop to latest follow-up in VAS (6.8 vs. 3.2, P < 0.000) and DPQ (63.2 vs. 45.6, P = 0.000) in the entire cohort. Nineteen patients (33%) had a revision fusion surgery after their index TDR. Patients who had revision surgery had statistically significant worse outcome scores at last follow-up than patients who had no revision. Thirty patients (52.6%) would choose the same treatment again if they were faced with the same problem. This study demonstrated significant improvement in long-term clinical outcomes, similar to previously published studies, and two-thirds of the discus prostheses were still functioning at follow-up. However, there is still a lack of well-designed long-term studies, thus requiring further investigation. 3.